2016
DOI: 10.1002/ange.201609110
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐Free Enantioselective Oxidative Arylation of Alkenes: Hypervalent‐Iodine‐Promoted Oxidative C−C Bond Formation

Abstract: The enantioselective oxyarylation of (E)-6-aryl-1silyloxylhex-3-ene was achieved using al actate-based chiral hypervalent iodine(III) reagent in the presence of boron trifluoride diethyl etherate.T he silyl ether promotes the oxidative cyclization, and enhances the enantioselectivity.I n addition, the corresponding aminoarylation was achieved.Supportinginformation for this article can be found under: http://dx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 71 publications
0
9
0
Order By: Relevance
“…3a,3b,34 More recently, Fujita and co-workers also reported that such a I(III) + ⋯O interaction exists even in acetonitrile. 6b The formation of the strong I(III) + ⋯O interaction in 1a+ induces a conformational change of the benzylic group, resulting in disruption of halogen-π interactions and exposure of the highly electrophilic cationic I(III) center for subsequent substrate binding and activation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3a,3b,34 More recently, Fujita and co-workers also reported that such a I(III) + ⋯O interaction exists even in acetonitrile. 6b The formation of the strong I(III) + ⋯O interaction in 1a+ induces a conformational change of the benzylic group, resulting in disruption of halogen-π interactions and exposure of the highly electrophilic cationic I(III) center for subsequent substrate binding and activation.…”
Section: Resultsmentioning
confidence: 99%
“…The discovery of enantioselective molecular catalysts based on iodine (I/III) redox chemistry has added a new dimension to hypervalent iodine chemistry. 2 Many chiral hypervalent iodine reagents or catalysts (Figure 1) have been invented by the groups of Wirth, 3 Kita, 4 Ishihara, 5 Fujita, 6 Muñiz, 7 Legault 8 , and others, 9 to effect asymmetric transformations that would be difficult to accomplish otherwise. 2,10…”
Section: Introductionmentioning
confidence: 99%
“…Hypervalent iodine(III) compounds have been emerged as an efficient reagent in the dehydrogenative C−C bond formations [9] such as cross‐coupling reactions of arenes with different kinds of arenes, [10] aldehydes, [11a] active methines [11b] or simple alkanes, [11c] arylation of alkenes [12a,b] or alkynes, [12c,d] and iodonio‐Claisen rearrangement [13] . Some of these dehydrogenative reactions have been extended to the iodine(III)‐catalysis [14] .…”
Section: Methodsmentioning
confidence: 99%
“…Chiral hypervalent iodines have become attractive catalysts and mediators for asymmetric oxidation reactions. 17 20 These species have been successfully employed for a wide range of enantioselective C–C, 21 23 C–O, 24 28 and C–N 29 , 30 bond formation reactions using alkene derivatives as substrates. The groups of Kitamura, 31 Jacobsen, 32 and Gilmour 33 reported pioneering methods for catalytic fluorination of olefins with in situ generated iodine(III) fluorides.…”
Section: Introductionmentioning
confidence: 99%